Systemic chemokine-modulatory regimen combined with neoadjuvant chemotherapy in patients with triple-negative breast cancer - Jessica Young; Pawel Kalinski; Mateusz Opyrchal; Kathleen M Kokolus; Sacha Gnjatic; Jianming Wang; Shipra Gandhi; Kristopher Attwood; Tracey O’Connor; Kazuaki Takabe; Victoria Fitzpatrick; Eduardo Cortes Gomez; et al. (Journal for ImmunoTherapy of Cancer)
Background Higher cytotoxic T lymphocyte (CTL) numbers in the tumor microenvironment (TME) predict pathologic complete response (pCR) to neoadjuvant chemotherapy (NAC) and positive long-term outcomes in triple-negative breast cancer (TNBC). pCR to NAC is achieved only in 30–40% of patients. The combination of NAC with pembrolizumab increases the pCR rate but at the cost of immune-related adverse events (irAEs). Based on these considerations, we tested if systemic infusion of the chemokine modulatory regimen (CKM; selective toll-like receptor 3 (TLR3) agonist rintatolimod, interferon (IFN)-α2b, and cyclooxygenase-2 (COX-2) inhibitor celecoxib) regimen can be safely combined with NAC to enhance intratumoral CTL numbers and NAC effectiveness.Methods Phase I study NCT04081389 evaluated nine patients with early-stage TNBC who received 3 weeks of paclitaxel with CKM (dose-escalation of IFN-α2b), followed by 9 weeks of paclitaxel alone, dose-dense doxorubicin and cyclophosphamide, and surgery. Primary and secondary endpoints were safety and clinical efficacy, respectively.Results The combination treatment was well-tolerated with no dose-limiting toxicities or irAEs. 5/9 patients achieved pCR and one patient had microinvasive disease (ypTmic). We observed elevated IFN signature and uniform decreases in CTL numbers (average 8.3-fold) in the blood of all treated patients. This was accompanied by reciprocal uniform increases in CD8β (overall 5.9-fold), CD8α/FoxP3 (2.11-fold), and CCL5 (4.73-fold) transcripts in TME, particularly pronounced in patients with pCR. Multiplex immunohistochemistry revealed selectively increased numbers of CTL (but not regulatory T cells) in both the epithelial and stromal tumor compartments and early decreases in the numbers of αSMA+ vascular/stromal cells in the tumors of all pCR patients.Conclusions Combined paclitaxel/CKM regimen was safe, with desirable TME changes and preliminary indications of promising pCR+ypTmic of 66%, comparable to the combination of NAC with pembrolizumab.